Kenduri Sko : Women As Leadership Heritages In The Tradition Of The Pengasi Lama Village Bukit Kerman District, Kerinci Regency - Putra, Martias (Jurnal Kajian Islam Interdisipliner, 2022)
Kenduri Sko can make women take the highest throne to become heirs to the traditional leadership of Pengasi Lama Village, This research uses a qualitative approach, with data collection techniques in the form of writing, or field observations. and various other data that are transformed or made in text form. The results showed that in the custom of Pengasi Lama Village, women who have been given the trust by the customary institution, women are very firm in maintaining the heirlooms that have been given, so this tradition is still preserved and sustainable until now. Historically, women can hold the highest throne in holding heirlooms, this is the result of the agreement of the previous ancestors. So that based on the analysis of local wisdom, the tradition of the transition of customary leadership in Pengasi Lama Village can be said to be a form of tradition from culture, which was left by the ancestors. [Fokus permasalahan dalam artikel ini adalah bagaimana ritual adat dalam Kenduri Sko yang dapat menjadikan perempuan mengambil tahta tertinggi menjadi pewaris kepemimpinan adat Desa Pengasi Lama, Penelitian ini menggunakan pendekatan kualitatif, dengan teknik pengumpulan data berupa tulisan, atau pengamatan lapangan. dan berbagai data lainnya yang ditransformasikan atau dibuat dalam bentuk teks. Hasil penelitian menunjukkan bahwa dalam adat Desa Pengasi Lama, perempuan yang telah diberi kepercayaan oleh lembaga adat maka perempuan sangat tegas menjaga dan merawat pusaka yang telah diberikan, Maka tradisi ini tetap dilestarikan dan berkelanjutan hingga sekarang. Secara historis perempuan dapat memegang tahta tertinggi dalam memegang benda pusaka hal ini hasil dari kesepakatan para leluhur. Berdasarkan analisis kearifan lokal tradisi peralihan kepemimpinan adat Desa Pengasi Lama dapat dikatakan sebagai bentuk tradisi dari kebudayaan, yang ditinggalkan oleh para leluhur.]